Needle-Stick Injuries in Ophthalmic Practice - Alfarhan A; Al-Swailem S; Alobaid M; Ahmad K; Khan R (Dove Medical Press, 2023)
Abdulrahman Alfarhan,1 Samar Al-Swailem,2,3 Mohannad Alobaid,4 Khabir Ahmad,3 Ruhi Khan5 1Fellowship and Residency Training Program, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Anterior Segment Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 3Research Department, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 4Department of Ophthalmology, King Saud Medical City, Riyadh, Saudi Arabia; 5Medicine Department, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Abdulrahman Alfarhan, King Khaled Eye Specialist Hospital, Riyadh, 14611, Saudi Arabia, Email Farhan.med011@gmail.comPurpose: Needle-stick injuries (NSI) are a prominent route by which blood-borne infections are transmitted. The unique microsurgical nature of ophthalmic practice constitutes an additional risk to sustain injury. This study aimed to identify the epidemiological profile of needle-stick injuries in a tertiary eye center and to evaluate the implemented safety policy in preventing sharp injuries.Methods: This was a retrospective cross-sectional study of all sharp injuries that occurred at King Khalid Eye Specialist Hospital (KKESH). Data on all reported sharp injury incidents from 2013 to 2021 were collected. The mechanisms of injury, context, location, and type of prick were collected and analyzed. Also, this study involved an institution-based survey for all ophthalmic staff.Results: Two hundred and one sharp injury incidents were reported over 9 years. Physicians sustained 46.8% (n=94) of injuries, followed by nurses and ophthalmic technicians, 40.8% (n=82) and 7% (14); respectively. Operating and treatment rooms were the locations of 60.7% of incidents, whereas outpatient clinics and emergency rooms accounted for 19.4% and 13.4% of injuries, respectively.Conclusion: The current findings add to the growing body of literature on the importance of NSI prevention and reporting strategies. In the present study, sharp injuries were most commonly encountered by ophthalmic staff in the operating rooms. Continuous staff education on handling sharp instruments, encouraging anonymous reporting, and up-to-date revisions of guidelines and policies are of paramount importance to lessen the burden of sharp injuries.Keywords: needle stick injury, sharp injury, occupational exposure, ophthalmology